CariPapa CPRG: botanical antiseptic & mosquito repellent cream / Ummu Umairah Armayni … [et al.] - Armayni, Ummu Umairah; Md Yusof, Nuruljannah; Ahmad, Mohd Sharil; Abd Aziz, Rosmawati; Ismail, Nahlah Elkudssiah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Mosquitoes are one of the vital vectors of diseases and nuisance pests. Repellent agent aids in minimizing the contact with mosquitoes. Therefore, natural evidence plant based mosquito repellent is developed as an alternative to currently available synthetic chemical mosquito repellent that contains as such DEET, N, Ndiethyl-m-toluamide and pyrethrin that can be harmful to human health and environment. CariPapaCPRG, a dermatological mosquito repellent and antiseptic cream, is developed using innovative formulation and chosen extract of Carica papaya leaves that are available widely in Malaysia. CariPapaCPRG is safe to be applied by users due to its safety profiles and localised effect, hence lack of systemic absorption consequently lack of side and adverse effects, unless patients have hypersensitivity toward any of the incorporated ingredients. No biotoxicity of the carrier and excipients, with generally recognized as safe (GRAS) status. Aiding in prevention of mosquito-borne diseases as well as alleviate painful or uncomfortable mosquito bites, CariPapaCPRG with high potential of being commercialized will enhance the pleasure of repellent outdoor and indoor activities.